Sarcoidosis clinical picture governs alterations in type 17 T helper cell subset composition and cytokine profile - N. M. Lazareva; I. V. Kudryavtsev; O. P. Baranova; D. V. Isakov; M. K. Serebriakova; A. A. Bazhanov; N. A. Arsentieva; N. E. Liubimova; T. P. Ses’; M. M. Ilkovich; A. A. Totolian (Медицинская иммунология, 2023)
Immune cell hyperactivation along with cytokines they overproduce plays an important role in sarcoidosis and related disease pathogenesis. A central place in the immunopathogenesis of sarcoidosis is held by diverse cell-mediated reactions governed by T helper (Th) cell populations including Th17 subsets and relevant signature cytokines. We studied peripheral blood plasma samples of the patients with sarcoidosis (n = 123): 18% with acute and 82% with chronic course. The control group — samples from healthy volunteers (n = 43). T cell subset composition was assessed by flow cytometry. Cytokine concentrations (pg/mL) were measured by multiplex analysis using xMAP technology (Luminex). The level of “classical” Th17 turned out to be significantly reduced in acute vs chronic sarcoidosis: 28.3% vs 33.3% (p = 0.046). The level of “double-positive” Th17 (DP Th17) was significantly increased in chronic and acute vs control group: 31.7% and 34.2% vs 26.2% (p < 0.001 in both cases), without differences patient inter-group; “non-classical” Th17.1 were shown to have significantly reduced level only in chronic vs healthy subjects: 27.9% and 35.9% (p < 0.001). Clinical and laboratory diagnostic characteristics for blood DP Th17 levels in CD45RA-negative Th effector memory cells in sarcoidosis: in acute sarcoidosis vs healthy subjects, they were characterized by sensitivity — 82%; specificity — 71%, whereas in chronic: 67% and 56%, respectively. In patients with sarcoidosis vs healthy subjects were found to have significantly increased level of IL-12 (p70) — 1.3 vs 0.56, p = 0.028; IL-17A — 1.5 vs 0.43, p < 0.001; IFNγ — 4.1 vs 1.1, p < 0.001; TNFα — 21.7 vs 6.7, p < 0.001. Thus, CCR6+ Th17 and DP Th17 subsets and relevant signature cytokines are important in diagnostics of sarcoidosis of varying clinical course: a direct correlation was shown between the level of angiotensin-converting enzyme activity and percentage of memory DP Th17; disease progression vs regression had significantly reduced absolute number of total CD45RA- memory and CM Th17; extrapulmonary manifestations had a significantly increased percentage of DP Th17 CD45RA- and EM DP Th17; in chronic sarcoidosis are significantly increased concentration of IL-17A, IFNγ, IL-12 and positively correlation between IFNγ and the activity of angiotensin-converting enzyme.